Sentence Examples


  • (ab)(ac)bxcx = - (ab)(bc)axcx = 2(ab)c x {(ac)bx-(bc)axi = 1(ab)2ci; so that the covariant of the quadratic on the left is half the product of the quadratic itself and its only invariant.
  • For example, take the ternary quadratic (aixl+a2x2+a3x3) 2 =a2x, or in real form axi +bx2+cx3+2fx 2 x 3+ 2gx 3 x 1 +2hx i x 2.
  • The transition from prophecy to apocalyptic (Corot(aXi 7rrecv, to reveal something hidden) was gradual and already accomplished within the limits of the Old Testament.